Performing mundane materiality: Actor-Network Theory, global student mobility and a re/formation of 'social capital'. Issue 1 (2nd January 2019) - Salomão Filho, Alfredo; Kamp, Annelies
ABSTRACT: Social capital is a puzzling actor; made real by its allies. It has been 'out-there' in the form of scientific publications for decades. Although some characteristics are common to all elaborations of this theory (networks, trust, and norms), there remains confusion in determining a 'coherent concept' of social capital. In this paper, we make use of such 'incoherence gap' to open an experimental theoretical and, subsequently, analytical space. Based on empirical research with mobile students and assemblages of non-human actors, the paper offers two investigative gatherings. First, the Bourdieusian approach to 'social capital' is discussed, allowing relational ontologies to enter the scene . Second, consideration is given to issues of performativity and the relevance of materiality for empirical social capital investigations. Despite the degree of ontological security social capital has managed to achieve, we question the disregard for the performative role of non-human entities in the context of global student mobility.